Investigation on preferably oriented abnormal growth of CdSe nanorods along (0002) plane synthesized by henna leaf extract-mediated green synthesis - Rajan, P. Iyyappa; Vijaya, J. Judith; Jesudoss, S. K.; Kaviyarasu, K.; Lee, Seung-Cheol; Kennedy, L. John; Jothiramalingam, R.; Al-Lohedan, Hamad A.; Abdullah, M. Mahamad (ROYAL SOC, 2018)
The theme of this work is to highlight the significance of green plant extracts in the synthesis of nanostructures. In asserting this statement, herein, we report our obtained results on the synthesis of hexagonal CdSe nanorods preferably oriented along (0002) plane through henna leaf extract -mediated reaction along with a discussion about the structural, morphological and optical properties of the synthesized nanorods. The possible mechanism for the synthesis of CdSe nanorods was explored. The formation of nanorods along (0002) plane was confirmed by the relatively high intensity of the (0002) peak in X-ray diffraction pattern. To account for the experimentally realistic condition, we have calculated the surface energies of hexagonal CdSe surface slabs along the low indexed (0002), (1010) and (1120) plane surfaces using density functional theory approach and the calculated surface energy value for (0002) surface is 802.7 mJ m(-2), which is higher than (1120) and (1010) surfaces. On realizing the calculated surface energies of these slabs, we determined that the combination of (1120) and (1010) planes with lower surface energies will lead to the formation of CdSe nanorods growth along (0002) orientation. Finally, we argue that the design of new greener route for the synthesis of novel functional nanomaterials is highly desired.
Keywords: NANOPARTICLES; DEPOSITION; FILMS